Effect of bactericidal activity of three disinfectants on methicillin-resistant Staphylococcus aureus (MRSA) - Cesar Augusto Marchionatti Avancini; Jane Mari Corrêa Both (Universidade de Santa Cruz do Sul, 2017)
Background and Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) can cause hospital-acquired infections (HA-MRSA), community- acquired ones (CA-MRSA), and infections transmitted by pets and animals raised for food production (livestock-acquired or LA-MRSA). The conduct to control the transmission of these diseases requires a careful action against the causative agents on surfaces in the environment and the choice of disinfectants and antiseptics is crucial. The objective of the present study was to evaluate the effect of the bactericidal activity of sodium hypochlorite (SH), iodophor (I) and a quaternary ammonium compound (QAC), cetyl-trimethyl-ammonium chloride, commonly used in hospital and animal production settings, on 21 MRSA isolates and a control bacterium, and test the hypothesis of cross resistance of antibiotics and disinfectants. Methods: The bactericidal activity of four successive dilutions of the disinfectants was evaluated through the suspension test, using an initial inoculum population density of 107 CFU/mL, after contact times of 5, 15 and 30 minutes. Results: Five minutes of contact of SH 25 ppm, I 12.5 ppm and QAC 125 ppm sufficed to inactivate the reference bacterium S. aureus ATCC 6538 and all MRSA. Conclusions: Once the factors that influence the efficiency of disinfectants are controlled, sodium hypochlorite, iodophor and the quaternary ammonium compound are suitable for controlling MRSA in the sources of infection. No resistance relationship was observed in the methicillin-resistant isolates with these substances.